Developing knowledge management in law firm to compete with other law firms within asean region in asean economics community environment - Kurnia Winenda, Erwin; Hidayat Tjakraatmadja, Jann (The Indonesian Journal of Business Administration, 2016)
Abstract. The purpose â€“ The purpose of this research is to formulate a proper KM program which can be used and implemented by Hanafiah Ponggawa & Partners (HPRP) on its day to day business in order to improve its performance and competitive advantage in the incoming AEC market. Business Issue â€“ The declaration of ASEAN Economic Community will increase investment within ASEAN, from European, America also Middle East countries and make ASEAN region become the most prospective market in the world. This condition will be followed by the expansion of foreign law firms to Indonesia to protect their clientâ€™s investment in ASEAN region. With their international experiences and expertise for more than 50 years handling cases or projects world-wide, and also capital, independent Indonesian law firms will face the following obstacles in achieving their business goals in the AEC market: (i) Short of good and experienced human resources; (ii) clients which more prefer to engage foreign affiliated law firm who has more experiences and capabilities handling international transaction; and (iii) pricing competition. This condition urgently need to be noticed by partners as management in law firm as well as all lawyers, so it can compete with other law firms in the AEC environment and increase its performances and competitive advantage in the AEC environment on the following years. Design/methodology/approach â€“ Qualitative research id used as the methods in this research, by using interview and questionnaires to collect data. In this research the data collected through: 1. Interview process to partners, lawyers, managers of HPRP, and clients of HPRP in order to obtain more perspective and to find out the main problem in this research. 2. The questionnaires were distributed to all lawyers of HPRP and itâ€™s used as a tool to collect and record information related with the current and expectation condition of knowledge management implementation in HPRP. Findings â€“ Based on the analysis of current condition of HPRP related to KM implementation for variable of people, process and technology, it was found that HPRP is still lacking in the dimension on each variables which were contributed to the decreasing of the performance of HPRP. By using â€œthe Five Steps Knowledge Management Implementationâ€ concept from Garfield this research produce the appropriate KM formulation related to the conditions of HPRP. This KM formulation will be used in HPRP by emphasizing to increase the KM awareness, lawyers competencies and HPRP knowledge sharing as the KM Objectives.Â Keywords â€“ Law Firm, KM Program, KM Implementation.Â